2000
DOI: 10.1074/jbc.m003867200
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian GFRα-4, a Divergent Member of the GFRα Family of Coreceptors for Glial Cell Line-derived Neurotrophic Factor Family Ligands, Is a Receptor for the Neurotrophic Factor Persephin

Abstract: Four members of the glial cell line-derived neurotrophic factor family have been identified (GDNF, neurturin, persephin, and enovin/artemin). They bind to a specific membrane-anchored GDNF family receptor as follows: GFR␣-1 for GDNF, GFR␣-2 for neurturin, GFR␣-3 for enovin/artemin, and (chicken) GFR␣-4 for persephin. Subsequent signaling occurs through activation of a common transmembrane tyrosine kinase, cRET. GFR␣-4, the coreceptor for persephin, was previously identified in chicken only. We describe the clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
37
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 43 publications
6
37
0
Order By: Relevance
“…et al, 1997;Sanicola et al, 1997), GFRα-3 (Jing et al, 1997;Naveilhan et al, 1998;Trupp et al, 1998), and GFRα-4 . In vitro and in vivo studies indicate that each GFRα exhibits high affinity binding and potent RET activation (i.e., is "specific") when paired with a single trophic factor (Jing et al, 1996;Treanor et al, 1996;Baloh et al, 1997;Klein et al, 1997;Leitner et al, 1999;Masure et al, 1999;Masure et al, 2000;Lindahl 275 TOXICOLOGIC PATHOLOGY et al, 2001). The preferred interactions are GDNF-GFRα-1, NTN-GFRα-2, ART-GFRα-3, and PSP-GFRα-4.…”
Section: Introductionmentioning
confidence: 99%
“…et al, 1997;Sanicola et al, 1997), GFRα-3 (Jing et al, 1997;Naveilhan et al, 1998;Trupp et al, 1998), and GFRα-4 . In vitro and in vivo studies indicate that each GFRα exhibits high affinity binding and potent RET activation (i.e., is "specific") when paired with a single trophic factor (Jing et al, 1996;Treanor et al, 1996;Baloh et al, 1997;Klein et al, 1997;Leitner et al, 1999;Masure et al, 1999;Masure et al, 2000;Lindahl 275 TOXICOLOGIC PATHOLOGY et al, 2001). The preferred interactions are GDNF-GFRα-1, NTN-GFRα-2, ART-GFRα-3, and PSP-GFRα-4.…”
Section: Introductionmentioning
confidence: 99%
“…GFRa4, the RET co-receptor for the GFL persephin (PSPN), is highly expressed in thyroid C-cells and in MTC (Lindahl et al, 2000;Masure et al, 2000). These observations suggested that GFRa4 might play a role in development of MTC tumours in the context of MEN 2, and that mutations of this locus might also contribute to MEN 2 phenotypes.…”
mentioning
confidence: 87%
“…All GFRa4 isoforms lack the first cysteine-rich domain found in these proteins. The WTa isoform is most similar to other GFRas, containing two cysteine-rich domains, spanning seven alpha helices, and the conserved GPI-linkage (Figure 3), and has been shown to bind both RET and its soluble ligand PSPN and to stimulate RET phosphorylation and survival of neuronal cell types (Enokido et al, 1998;Masure et al, 2000;Lindahl et al, 2001). Compared to WTa, WTb lacks helices 4 and 5 (Figure 3) and has an odd number of cysteine residues that would result in an unpaired residue, potentially available for novel interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been estimated that Ͼ50% of human multi-exon genes are alternatively spliced (Modrek and Lee, 2002). Multiple alternatively spliced variants of GFR␣1 (Sanicola et al, 1997;Dey et al, 1998;Shefelbine et al, 1998), GFR␣2 Dolatshad et al, 2002), and GFR␣4 (Lindahl et al, 2000(Lindahl et al, , 2001Masure et al, 2000) have been reported. Similarly, alternative spliced isoforms of the coreceptors RET (Lorenzo et al, 1997;de Graaff et al, 2001;Lee et al, 2002) and NCAM (Povlsen et al, 2003;Buttner et al, 2004) have been reported.…”
Section: Introductionmentioning
confidence: 99%